Detection of human papillomavirus in early stage cervical carcinoma: Comparison of conventional and catalysed reporter deposition in situ hybridization. - Basheska, Neli; Kubelka-Sabit, Katerina; Yashar, Genghis; Prodanova, Irina; Zografski, George (Blackwell Publishing, 2002)
Introduction: Recently, alternative techniques have been developed to overcome the sensitivity limitation of conventional in situ hybridization (ISH), by signal amplification, which can be performed in diagnostic laboratories without the need for expensive equipment. Aims: The purpose of this study was to compare the efficiency and applicability of catalyzed reporter deposition (CARD) ISH, with those of conventional ISH in detection of human papillomavirus (HPV) in early stage cervical carcinomas. Material and Methods: Seventy-seven routinely processed specimens previously tested by conventional streptavidin-biotin-alkaline phosphatase ISH (PathoGene, Enzo Diagnostics), were reexamined by CARD-ISH performed by a biotinyl-tyramide-based detection system (GenPoint, DAKO). ISH was performed using commercial mixed biotinylated probes for HPV 6/11, 16/18, and 31/33/51 or 31/33. Discussion and Conclusion: The application of CARD-ISH increased the HPV detection rate from 33.8% (26/77) to 58.4% (45/77), the signal intensity, as well as the number of positive cells. CARD-ISH detection also enabled demonstration of multiple HPV infection in four cervical carcinomas. Diffuse and mixed staining patterns were more prevalent in conventional ISH, while a dot signal pattern presumably indicating viral integration, was highly predominant among CARD-ISH positive cases. CARD-ISH proved to be simple, fast, sensitive and effective at detecting low-copy of HPV in cervical carcinomas.
Keywords: in situ hybridization; signal amplification; human papillomavirus; cervical carcinoma